Tingkat Kemampuan Berpikir Kreatif Siswa dengan Kecerdasan Logis Matematis Sedang dalam Pemecahan Masalah Geometri - Asriningsih, Tafsillatul Mufida; Rahmawati, Ana; Lailah, Devi (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
This is a qualitative-descriptive research. The aims of this study is to describe the level of students creative thinking in geometry problem solving tasks. The subject in this research is a student in the average-level of logical-mathematical intelligence. The subject is on the 7th grade of MTs Al-Hikmah Janti Jombang. The research instrument is logical-mathematical intelligence test, creative thinking test, and interview sheet. The result of this study for fluency critera is student can make two shapes in different size. The result for flexibility criteria is student only use one way to determine the area of a shape, it is by using a formula for counting the area. The result for novelty criteria is student can not make some shapes which are different. All that result shows that student only fulfill one of creative thinking criteria, that is fluency critera. But student can not fulfill the other two criterias of of creative thinking they are flexibility and novelty. Therefore student’s level of creative thinking is on level 1 (almost not creative).